2017
DOI: 10.2147/ott.s137312
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipiodol deposition in HCC after TACE on the necrosis range of PMCT

Abstract: ObjectiveTo study the impact of lipiodol deposition in the lesion of hepatocellular carcinoma (HCC) after transarterial chemoembolization (TACE) on the necrosis area of percutaneous microwave coagulation therapy (PMCT).Materials and methodsA total of 44 patients with HCC with 56 nodules, with a size ranging from 1.5 to 3.5 cm, was selected in our study. About 23 patients (26 nodules) underwent PMCT treatment only as Group A and 21 patients (30 nodules) were treated by PMCT-combined TACE as Group B. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, hydrothorax and peritonitis were common complications caused by PMCT. 20 In this study, the higher incidence of hydrothorax in the TACE–PMCT group was found compared to other two groups, but hydrothorax can be resolved by applying albumin and diuretic. In addition, pulmonary metastasis, peritonitis, and hepatic encephalopathy were associated with the prognosis of MHCC patients by univariate analysis.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…However, hydrothorax and peritonitis were common complications caused by PMCT. 20 In this study, the higher incidence of hydrothorax in the TACE–PMCT group was found compared to other two groups, but hydrothorax can be resolved by applying albumin and diuretic. In addition, pulmonary metastasis, peritonitis, and hepatic encephalopathy were associated with the prognosis of MHCC patients by univariate analysis.…”
Section: Discussionmentioning
confidence: 46%
“… 23 TACE could alleviate the adverse cooling effect induced by abundant blood flow on microwave thermal coagulation by blocking the tumor vascular bed. 20 , 23 Seki et al 32 reported that the combination of TACE and PMCT might result in higher rates of necrosis and longer survival times compared to treatment with TACE or PMCT alone and improve the prognosis of HCC patients. Up to date, there are limited studies on the efficacy and safety of MHCC patients treated with TACE plus PMCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the treatment modalities for HCC is transcatheter arterial chemoembolization (TACE), which is appropriate for stage B HCC according to Barcelona Clinic Liver Cancer staging system (3). TACE experienced many technical developments as new drugs and delivery systems were developed, but the conventional approach, using Lipiodol emulsion mixed with doxorubicin followed by complete embolization is still one of the most used methods worldwide (4). The follow-up of TACE-treated HCC is performed by computed tomography (CT) and/or magnetic resonance imaging (MRI).…”
Section: Introduction Introductionmentioning
confidence: 99%